2018
DOI: 10.1021/acs.jpcc.8b06668
|View full text |Cite
|
Sign up to set email alerts
|

SnP3: A Previously Unexplored Two-Dimensional Material

Abstract: We predict SnP 3 to be an easily exfoliable and dynamically stable twodimensional (2D) material with thickness-dependent electronic properties. On the basis of density functional theory calculations, we show that mono-and bilayer SnP 3 has relatively low cleavage energies of 0.71 and 0.45 J m −2 , lower than several other 2D materials and comparable to that of graphene (0.32 J m −2 ). Mono-and bilayer SnP 3 have an indirect band gap of 0.83 and 0.55 eV, respectively, and the magnitude of the gap can be tuned b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 59 publications
7
71
0
Order By: Relevance
“…Electrostatic potential indicates the minimum energy that electron must absorb when it escapes from a material, which shows relationship with chemical stability [18,[20][21][22]. Figure 3 Water splitting is a clean and effective way of oxygen and hydrogen production.…”
Section: Structure and Stabilitymentioning
confidence: 99%
“…Electrostatic potential indicates the minimum energy that electron must absorb when it escapes from a material, which shows relationship with chemical stability [18,[20][21][22]. Figure 3 Water splitting is a clean and effective way of oxygen and hydrogen production.…”
Section: Structure and Stabilitymentioning
confidence: 99%
“…Liu and co-workers 25 theoretically predicted the SnP 3 monolayer with an ultralow energy barrier (0.03 eV) for Na diffusion. However, the reported band gaps of GeP 3 (0.55 eV), 23 SnP 3 (0.72 eV), 22,26 and InP 3 (1.14 eV) 21 monolayers are relatively narrow so that they are unsuitable for photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have conducted many studies on 2D Group IV-P compounds, including theoretical predictions and experimental explorations. [23][24][25][26][27][28][29][30][31] For example, Zeng and colleagues reported that monolayer SiP has a direct E g of 2.59 eV, which is different from the indirect E g for its bulk counterpart. [23] Moreover, monolayer SiP exhibits excellent dynamic and thermodynamic stability even at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Bhowmick and colleagues predicted that layered SnP 3 has a high carrier mobility, tunable E g , and large optical absorption coefficient, implying that SnP 3 has great potential as a NLO material. [25] In regard to 2D Ge-P compounds, including GeP, [26,27] GeP 2 , [28] GeP 3 , [29,30] and GeP 5 , [31] some significant investigations have been performed. The calculation shows that GeP 3 possesses a higher chemical stability than BP, a high carrier mobility (8.84 × 10 3 cm 2 V −1 s −1 ), a moderate tunable E g from 0 to 0.55 eV and pronounced light absorption in the spectral range from 600 to 1400 nm, [29] which indicates that GeP 3 is a promising candidate for optoelectronic and photonic application.…”
Section: Introductionmentioning
confidence: 99%